Students’ Learning Strategies for Developing Speaking Ability - Sofyan A. Gani; Dian Fajrina; Rizaldy Hanifa (Studies in English Language and Education, 2015)
This study was done to study the learning strategies used by both low and high performance speaking students in developing their speaking skills as well as the differences between the learning strategies used by both groups of learners. The reason for conducting this research was the fact that the competency of many students in speaking English was still considered unsatisfactory in Banda Aceh. We postulated that one aspect involved in the process of developing speaking skills was the learning strategies used by the learners. In this study, the data was collected through field research by means of documents, questionnaires, and interviews. The result of this study indicated that high performance speaking students had better balance in using all kinds of learning strategies (memory, cognitive, compensatory, metacognitive, affective, and social) for enhancing their speaking skills; the same could not be found with low performance speaking students. Besides, the high performance students employed more learning strategies consciously and appropriately compared to the low performance students. Based on the research results, it is suggested that students should be trained to be more aware of their own speaking learning strategies. They should use appropriate language learning strategies more consciously, purposefully, and frequently to be more successful in developing their speaking skills.